Practicality of Electronic Assessment to Assess Student Critical Thinking Ability on Circular Motion Material - Nuri Yuliani; Fatni Mufit; Festiyed Festiyed; Emiliannur Emiliannur (Universitas Negeri Padang in collaboration with Association of Mathematics and Natural Sciences Institution for Education of Teaching Staff Indonesia (AMLI), 2026)
This study is motivated by the importance of critical thinking skills as essential 21st-century competencies that need to be effectively trained and assessed in physics learning, particularly in circular motion material. However, existing assessments are still limited, less interactive, lack contextual representation of real phenomena, and do not provide optimal feedback to measure students’ critical thinking abilities. Therefore, this study aims to determine the practicality of an electronic assessment developed to assess students’ critical thinking skills on circular motion material. The assessment instrument was developed using Wizer.me and Google Sites platforms by integrating critical thinking indicators proposed by Ennis. This research employed the Development Research method using the Plomp development model combined with Tessmer’s formative evaluation, which includes self-evaluation, one-to-one evaluation, and small group evaluation stages. Data were collected through a practicality questionnaire and analyzed using quantitative descriptive methods. The results showed that in the one-to-one evaluation stage, the average practicality score was 81% based on students’ responses and 92% based on teachers’ responses, both categorized as very practical. In the small group evaluation stage, the average score was 88%, also categorized as very practical. These findings indicate that the developed electronic assessment is easy to use, engaging, efficient, and beneficial in helping teachers assess students’ critical thinking abilities. Therefore, this electronic assessment is feasible to be used as an alternative assessment tool in physics learning.